Improving the performance of TFC membranes via chelation and surface reaction: applications in water desalination. Issue 17 (15th April 2016) - Ali, Mohamed E. A.; Hassan, Fathy M.; Feng, Xianshe
Abstract : We modified TFC membranes via a series of chemical and surface reactions. A nascent polyamide (PA) active layer was prepared by interfacial polymerization and composited with GO nanosheets then reacted with CuCl2 ·2H2 O. Finally, the composite membrane was treated with NH4 OH solutions. Abstract : Here we report modification of thin film composite (TFC) membranes via a series of chemical and surface reactions. Initially, the nascent polyamide (PA) active layer was prepared by interfacial polymerization and composited with graphene oxide (GO) nanosheets and then reacted with cupric chloride dihydrate (CuCl2 ·2H2 O). Finally, the composited membrane was treated by a reaction with ammonium hydroxide (NH4 OH) solution. The chemical modifications of the PA active layer included the formation of a polyamide–copper–graphene oxide complex (PA–Cu 2+ –GO), whereas, the surface modifications, mineralization, include the formation of copper hydroxide [Cu(OH)2 ] on the membrane surface through a reaction between the residual CuCl2 ·2H2 O and NH4 OH solution. The results of the compositional analysis of mineralized membranes showed that the active layer is fully cross-linked, with Cu 2+ chelated with amide nitrogen and coordinated with the carbonyl groups. The membrane performance was evaluated using a cross-flow apparatus at 2000 mg L −1 NaCl solution, 25 °C and a pressure of 15 bar. The mineralized membrane with optimum concentrations of copper chloride and ammonium hydroxide of 0.125 molar and 0.1%, respectively, and a reaction time of 1 minute showed a higher pure water permeability and solute water flux (44.25, 33.77 L m −2 h −1 ) compared to the pristine TFC membrane (21.36, 20.2 L m −2 h −1 ) with an excellent salt rejection (≥98.5%). Moreover, the mineralized membranes were found to resist chlorine attack and fouling adsorption more than the non-treated TFC membrane.